SAT-287 Mild Perinatal Undernutrition Results in Underweight Pups and a Premature Neonatal Leptin Surge - Miles, Tiffany K (J Endocr Soc, 2020)
Malnutrition causes dysregulated pituitary function, which may in part be due to lowered leptin signals. We showed that loss of somatotrope leptin receptors in mice reduces growth hormone (GH) secretion and promotes metabolic dysfunction in adults. More recently, we showed that adult male mice fasted for 12 or 24 hours also had significantly lowered GH secretion, which correlated with a 94% reduction in serum leptin. Malnutrition may result in changes in the leptin surge during neonatal development in rodents or the third trimester in humans. Severe (50% reduction) maternal undernutrition (1) blunted the surge in rodents, however less severe undernutrition (30% reduction) caused a premature leptin surge (2). Both studies reported that pups showed metabolic dysfunction as adults. In our studies of leptin regulation of somatotropes, we tested the more severe calorie restriction model and discovered significant pup and maternal loss. We then elected to develop a milder undernutrition model, which may relate more closely to society’s nutritional challenges with the objective of determining if the timing of the leptin surge had shifted. This maternal undernutrition study consisted of dams fed ad libitum (fed) and pair fed dams receiving 20% reduced caloric intake (undernourished). Undernutrition started at E15 and ended with sacrifice at various times during the leptin surge. While nursing, the undernourished dams did not lose weight, but their weight gain was reduced to 45% of that of fed dams. We have collected data from 177 neonatal pups and 19 fed or undernourished dams. At PND5 and PND10, pups from undernourished moms weighed significantly less (16.3% and 21.8%) than pups from fed dams. Additionally, weanlings (PND 21) from underfed dams exhibited a 28.04% reduction in weight and an 8.43% reduction in nose to anus length (p = 0.0005) compared to pups from control fed dams. The timing of the leptin surge in pups from fed dams was normal in female pups. However, pups from mildly undernourished dams had “premature” leptin surges that peaked 2 days earlier than normal. Ongoing studies are testing metabolic function in these mice, as adults, to determine their sensitivity to a 45% high fat diet and the impact on somatotrope functions. This model demonstrates that even a 20% reduction in nutrition will negatively impact offspring and shift the timing of the leptin surge. 1. Delahaye F, Breton C, Risold PY, Enache M, Dutriez-Casteloot I, Laborie C, Lesage J, Vieau D. Maternal perinatal undernutrition drastically reduces postnatal leptin surge and affects the development of arcuate nucleus proopiomelanocortin neurons in neonatal male rat pups. Endocrinology 2008; 149:470-475 2. Yura S, Itoh H, Sagawa N, Yamamoto H, Masuzaki H, Nakao K, Kawamura M, Takemura M, Kakui K, Ogawa Y. Role of premature leptin surge in obesity resulting from intrauterine undernutrition. Cell metabolism 2005; 1:371-378